2000
DOI: 10.1128/jb.182.20.5916-5918.2000
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of Poly(3-Hydroxybutyrate) inRalstonia eutropha

Abstract: Ralstonia eutropha H16 degraded (mobilized) previously accumulated poly(3-hydroxybutyrate) (PHB) in the absence of an exogenous carbon source and used the degradation products for growth and survival. Isolated native PHB granules of mobilized R. eutropha cells released 3-hydroxybutyrate (3HB) at a threefold higher rate than did control granules of nonmobilized bacteria. No 3HB was released by native PHB granules of recombinant Escherichia coli expressing the PHB biosynthetic genes. Native PHB granules isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(116 citation statements)
references
References 13 publications
(4 reference statements)
2
114
0
Order By: Relevance
“…In vivo, the levels of PHB in wt and ⌬phaZ1 R. eutropha strains were monitored. PHB depolymerase activity in crude extract was also measured (4,14). The results from these studies suggested that at least one additional intracellular depolymerase was required to account for PHB utilization.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…In vivo, the levels of PHB in wt and ⌬phaZ1 R. eutropha strains were monitored. PHB depolymerase activity in crude extract was also measured (4,14). The results from these studies suggested that at least one additional intracellular depolymerase was required to account for PHB utilization.…”
Section: Resultsmentioning
confidence: 84%
“…Previous studies demonstrated the presence of the intracellular depolymerase PhaZ1 in R. eutropha (4,14,15). In vivo, the levels of PHB in wt and ⌬phaZ1 R. eutropha strains were monitored.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The emulsion was heated to remove chloroform and dialyzed for 24 h against 0.01% (wt/vol) sodium deoxycholate at room temperature. Native PHB was isolated from W. eutropha H16 and purified by glycerol density gradient (10). The 3HB oligomers were prepared as described previously (42).…”
Section: Poly(3-hydroxybutyrate) (Phb) a Homopolymer Of R(ϫ)-3-mentioning
confidence: 99%
“…Only recently, three intracellular PHA depolymerases (PhaZ1, PhaZ2 and PhaZ3) and a 3HB-oligomer hydrolase (previously also designated PhaZ2), which hydrolyse PHAs and the cleavage products produced by PhaZs, were cloned and characterized in R. eutropha (Saegusa et al, 2001(Saegusa et al, , 2002Kobayashi et al, 2003;York et al, 2003). However, in contrast to the extracellular degradation of PHAs (Jendrossek et al, 1996Jendrossek & Handrick, 2002), relatively little is known about intracellular mobilization and degradation in PHA-accumulating cells (Handrick et al, 2000;Saito & Kobayashi, 2002).…”
Section: Introductionmentioning
confidence: 99%